Osteogenic scaffolds based on fumaric/N-isopropylacrylamide copolymers: Designed, properties and biocompatibility studies - Bravi Costantino, Maria Leticia (2020)
In the present work the creation of a new biomaterial aimed at bone tissue regeneration is shown, covering the synthesis of the polymers, the material design and their exhaustive physicochemical and biological characterization. The copolymers of dioctyl fumarate (DOF) and N-isopropylacrylamide (NIPAM) were synthetized and characterized by size exclusion chromatography, 1H NMR and its thermal properties were studied by DSC and TGA analyses. Based on their properties, two copolymers with different DOF content were selected as raw material to design scaffolds for bone tissue regeneration. The scaffolds were prepared by casting and electrospinning technique, giving rise to biomaterials with particular chemical and topographic surface which were characterized by water contact angle and scanning electron microscopy (SEM) analysis. The cytotoxicity and biodegradation by murine macrophage RAW 264.7 cells was assay, while biocompatibility and osteogenic induction were made using bone marrow progenitor cells (BMPC). None of the biomaterials obtained showed cytotoxicity. The biological properties suggest that the cells adhere and proliferate better on biomaterials with higher DOF content and fibrous morphology. All scaffolds support osteoblastic cell differentiation, but to a greater extent on the biomaterial that has higher DOF content prepared by casting. Altogether, our results suggesting that these biomaterials could be useful in the bone tissue engineering.